2016
DOI: 10.4184/asj.2016.10.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Spinal Hemangioblastoma Location and Age

Abstract: Study DesignRetrospective case series.PurposeTo investigate the relationship between tumor location and clinical characteristics.Overview of LiteratureHemangioblastoma is a rare disease that develops in the central nervous system. Magnetic resonance imaging (MRI) is useful to evaluate hemangioblastomas. Hemangioblastoma's location is designated as intramedullary, intramedullary+extramedullary, or extramedullary by MRI.MethodsWe analyzed 11 patients who underwent surgery for spinal hemangioblastoma. Using T1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…[ 3 - 5 ] Of interest, Yasuda et al . reported that extramedullary hemangioblastomas had smaller syrinxes versus intramedullary and intramedullary+extramedullary lesions,[ 6 ] this finding might help distinguish between extramedullary hemangioblastomas versus meningioma and other tumors.…”
Section: Discussionmentioning
confidence: 95%
“…[ 3 - 5 ] Of interest, Yasuda et al . reported that extramedullary hemangioblastomas had smaller syrinxes versus intramedullary and intramedullary+extramedullary lesions,[ 6 ] this finding might help distinguish between extramedullary hemangioblastomas versus meningioma and other tumors.…”
Section: Discussionmentioning
confidence: 95%
“…Há predominância no sexo masculino na relação de 2:1 1 , com variação na literatura até 5,5:1 10 e ocorrência em adultos jovens, com pico de incidência entre 35 e 45 anos. Yasuda et al 10 descreveram uma maior média de idade em hemangioblastomas extramedulares puros em comparação aos intramedulares e intra/extramedulares. Hemangioblastomas extradurais puros são raros com apenas quatro casos descritos na literatura mundial 7 .…”
Section: Figura 1 Rm De Coluna Vertebral (A Corte Sagital; B Transunclassified
“…A RM é padrão-ouro no diagnóstico de hemangioblastoma do canal espinhal, o tumor em comparação com a medula espinhal apresentando-se de hipo-a isointenso nas sequências ponderadas em T1, captação de contraste, e de iso-a hiperintenso nas sequências ponderadas em T2, os extramedulares não causam alteração no sinal 10,17,22 .…”
Section: Figura 1 Rm De Coluna Vertebral (A Corte Sagital; B Transunclassified
See 1 more Smart Citation
“…14,15 There are two main different types: at the cervical level it is usually the cellular type, and at the level of the conus ependymoma it is usually the myxopapillary type. They are slow-growing tumors and characteristically show vertebral scalloping with enlarged foramen, erosion of the pedicle or laminar thinning, intratumoral cyst, and hemorrhage with sometimes fluid-fluid levels 16 (►Figs. 5 and 6).…”
Section: Intramedullary Lesion With Mass Effectmentioning
confidence: 99%